(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the reforms implemented in the field of education of our country, the role of legal democratic and civil society in the education of high moral youth, the analysis of education in a number of decisions and decrees of the President of the Republic of Uzbekistan, the actual implementation of the state policy on youth , the study of cultural-spiritual heritage and its effective use, the development of axiological attitude of young people to democratic processes, and the philosophical factors that should be taken into account when educating them in the national spirit are given.